2020
DOI: 10.1055/s-0040-1715104
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic Value of Neutrophil to Lymphocyte Ratio and Mean Platelet Volume on Early Onset Neonatal Sepsis on Term Neonate

Abstract: By setting out from increased neutrophil count, decreased lymphocyte count, and increased mean platelet volume (MPV), which is a result of the effect of inflammation on blood cells, we aimed to investigate whether neutrophil to lymphocyte ratio (NLP) and MPV can be used as an auxiliary parameter for the diagnosis of early-onset neonatal sepsis (EOS). This study was conducted by analyzing term neonates with EOS and physiological jaundice who were admitted to the neonatal intensive care unit of Izmir Katip Celeb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
23
1
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(29 citation statements)
references
References 28 publications
3
23
1
2
Order By: Relevance
“…But only one study investigated the CRP/MPV ratio in children with pneumonia [28]. Various other ratios are being used in the diagnosis of neonatal sepsis, which includes CRP/albumin ratio [29], neutrophil-lymphocyte ratio [15,[30][31][32][33], and platelet to lymphocyte ratio [34].…”
Section: Introductionmentioning
confidence: 99%
“…But only one study investigated the CRP/MPV ratio in children with pneumonia [28]. Various other ratios are being used in the diagnosis of neonatal sepsis, which includes CRP/albumin ratio [29], neutrophil-lymphocyte ratio [15,[30][31][32][33], and platelet to lymphocyte ratio [34].…”
Section: Introductionmentioning
confidence: 99%
“…Septic preterm neonates had considerably greater NLR than full-term and preterm controls, with a value of 3.4. Some research came to the same conclusion: septic neonates had higher levels of neutrophils and NLR than controls, which was statistically significant [15,9].…”
Section: Discussionmentioning
confidence: 88%
“…An study conducted by Karabulut and Alatas found that variations in gestational age, birth weight, and delivery method might account for the broad cutoff values, sensitivity, and specificity of traditional indicators routinely employed in newborn sepsis diagnosis [15].…”
Section: Discussionmentioning
confidence: 99%
“…For instance, higher CRP levels were reported to be associated with post-septal disease in a recent study [10]. NLR is a parameter which is studied in bacterial infections such as neonatal sepsis, urinary tract infection and community acquired pneumonia [13][14][15]. A recent study which included 243 children with orbital infections, of whom 51 (20.6%) had OC, found that an NLR value of > 3.14 could differentiate OC from PC with a sensitivity of 75.5% and a speci city of 77.4% [16].…”
Section: Discussionmentioning
confidence: 99%